(untitled) - Khan, Haider A. (New York, 2003)
Haider Khan's book goes beyond the study of catch-up technology and raises the question of innovation processes that are the key to the future growth and prosperity of the East Asian economies. This is particularly important in the aftermath of the Asian financial crises that have cost these economies much. How can newly industrialized economies achieve cohesive systems of innovation for sustainable growth? The author offers a novel theory of innovation systems with concrete case studies to illustrate its usefulness.
Keywords: Technological innovations,Finance,Economic conditions; Economic aspects; East Asia,East Asia,East Asia